Chimeric antigen receptor‐engineered cytokine‐induced killer cells overcome treatment resistance of pre‐B‐cell acute lymphoblastic leukemia and enhance survival. Issue 8 (11th June 2016) - Oelsner, Sarah; Wagner, Juliane; Friede, Miriam E.; Pfirrmann, Verena; Genßler, Sabrina; Rettinger, Eva; Buchholz, Christian J.; Pfeifer, Heike; Schubert, Ralf; Ottmann, Oliver G.; Ullrich, Evelyn; Bader, Peter; et al.
Abstract : Pre‐emptive cancer immunotherapy by donor lymphocyte infusion (DLI) using cytokine‐induced killer (CIK) cells may be beneficial to prevent relapse with a reduced risk of causing graft‐ versus ‐host‐disease. CIK cells are a heterogeneous effector cell population including T cells (CD3 + CD56 − ), natural killer (NK) cells (CD3 − CD56 + ) and natural killer T (T‐NK) cells (CD3 + CD56 + ) that exhibit non‐major histocompatibility complex (MHC)‐restricted cytotoxicity and are generated by ex vivo expansion of peripheral blood mononuclear cells in the presence of interferon (IFN)‐γ, anti‐CD3 antibody, interleukin‐2 (IL‐2) and interleukin‐15 (IL‐15). To facilitate selective target‐cell recognition and enhance specific cytotoxicity against B‐cell acute lymphoblastic leukemia (B‐ALL), we transduced CIK cells with a lentiviral vector encoding a chimeric antigen receptor (CAR) that carries a composite CD28‐CD3ζ domain for signaling and a CD19‐specific scFv antibody fragment for cell binding (CAR 63.28.z). In vitro analysis revealed high and specific cell killing activity of CD19‐targeted CIK/63.28.z cells against otherwise CIK‐resistant cancer cell lines and primary B‐ALL blasts, which was dependent on CD19 expression and CAR signaling. In a xenograft model in immunodeficient mice, treatment with CIK/63.28.z cells in contrast to therapy with unmodified CIK cells resulted in complete and durable molecular remissions of established primary pre‐B‐ALL. Our results demonstrate potent antileukemic activity of CAR‐engineered CIK cells in vitro and in vivo, and suggest this strategy as a promising approach for adoptive immunotherapy of refractory pre‐B‐ALL. Abstract : What's new? Cytokine‐induced killer (CIK) cells are used in pre‐emptive immunotherapy for high‐risk cancer patients. In this study, the authors asked whether the cytotoxicity of CIK cells could be enhanced against B‐ALL. They engineered CIK cells to target a B‐cell‐specific antigen (CD19) by inserting a vector encoding a chimeric antigen receptor (CAR). Compared to controls, the targeted CIK cells were highly cytotoxic in vitro, and they also induced durable remissions in a mouse model of human B‐ALL. CAR‐engineered CIK cells may thus be a promising approach for immunotherapy of refractory leukemias.